Learn Bash Shell scripting for automation. (Packt Publishing, 2023)
Bash shell scripting is a programming language to automate tasks and interact with the operating system in Unix/Linux. It allows users to write scripts that execute commands, make decisions based on conditions, and manipulate data. Using variables, loops, and functions, users can create powerful scripts to streamline repetitive tasks, manage system configurations, and improve system automation efficiency. The course elaborates on Bash shell scripting in Unix/Linux environments. The course covers basic shell script writing to advanced automation techniques. You will learn about environment setup, variable handling, conditional statements, loops, and functions. The course delves into essential Unix filters such as grep, awk, and sed to manipulate data. It covers working with remote servers, interacting with REST APIs, and handling regular expressions. With practical projects and real-world examples, you will gain hands-on experience in automating tasks, enhancing productivity, and becoming proficient in Linux/Unix administration and automation. Upon completion, you will be skilled in Bash scripting for Unix/Linux environments, automated tasks, managing configurations, and manipulating data effectively. The course covers conditional statements, loops, functions, and practical projects, providing hands-on experience. What You Will Learn Write and execute Bash shell scripts in Unix/Linux environments Utilize filters such as grep, awk, and sed for data manipulation Apply conditional statements, loops, and functions for decision-making Interact with remote servers and REST APIs Use regular expressions for text pattern matching Practical projects enhance Linux/Unix administration and DevOps skills Audience The course is aimed at professionals in Unix/Linux environments to become proficient in Bash shell scripting, suitable for automation engineers, system administrators, DevOps engineers, software developers, database administrators, AWS cloud administrators, and IT professionals with basic knowledge of Linux/Unix commands. Basic knowledge of Linux/Unix commands is required for this course. No experience in Bash shell scripting is necessary, making it suitable for beginners. You should have access to a Unix-like OS (Linux, Unix, macOS) to practice the concepts taught in the course. About The Author VRTechnologies: VRTechnologies is a seasoned DevOps automation consultant with a specialization in cloud and DevOps. With a wealth of experience, they have successfully trained over 400 students through comprehensive automation courses covering Shell, Python, and Ansible. With six years of training expertise, VRTechnologies' commitment to staying at the forefront of technology trends is unmatched, ensuring that students receive the most up-to-date knowledge. Their passion for learning and teaching drives them to meticulously research and prepare each course, offering hands-on demonstrations from the basics to advanced concepts. Join VRTechnologies on a transformative learning journey and unlock the power of automation in your career.